Sedimentary alkenone distributions reflect salinity changes in the Baltic Sea over the Holocene. (December 2016) - Warden, Lisa; van der Meer, Marcel T.J.; Moros, Matthias; Sinninghe Damsté, Jaap S.
Highlights: Changes in salinity can cause changes in haptophyte species composition. Alkenone distributions and δD of alkenones co-vary with salinity in the Baltic Sea. Alkenone distributions and δD of alkenones have potential as a paleosalinity proxy. C36:2 alkenone is reported in the Baltic Sea for the first time. δD of the C36:2 alkenone suggests it comes from a low-salinity adapted haptophyte. Abstract: The Baltic Sea has had a complex salinity history since the last deglaciation. Here we show how distributions of alkenones and their δD values varied with past fluctuations in salinity in the Baltic Sea over the Holocene by examining a Holocene record (11.2–0.1 cal kyr BP) from the Arkona Basin. Major changes in the alkenone distribution, i.e., changes in the fractional abundance of the C37:4 Me alkenone, the C38:2 Et alkenone and a C36:2 Me alkenone, the latter which has not been reported in the Baltic Sea previously, correlated with known changes in salinity. Both alkenone distributions and hydrogen isotopic composition suggest a shift in haptophyte species composition from lacustrine to brackish type haptophytes around 7.7–7.2 cal kyr BP, corresponding with a salinity change that occurred when the connection between the basin and the North Sea was re-established. A similar salinity change occurred in the Black Sea. Previously published alkenone distributions and their δD values from the Black Sea were used to reconstruct Holocene changes in surface water salinity and, hence, it was shown that the unusual C36:2 alkenone dominates the alkenone distribution at salinities of 2–8 ppt (g/kg). This information was used to corroborate the interpretations made about salinity changes from the data presented for the Baltic Sea. Low and variable salinity waters in the Baltic Sea over the Holocene have led to a variable alkenone-producing haptophyte community composition, including low salinity adapted species, hindering the use of the unsaturation ratios of long-chain alkenones for sea surface temperature reconstruction. However, these alkenone based indices are potentially useful for studying variations in salinity, regionally as well as in the past.